2021
DOI: 10.3390/nu13020522
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Diet Quality and Related Sociodemographic, Health, and Occupational Characteristics among Workers in Spain: Results from Three Consecutive National Health Surveys (2006–2017)

Abstract: Poor dietary practices are commonly reported in working populations from different economic sectors, resulting in increased absenteeism and a decrease in productivity. The aims of this study were to describe the frequency of food consumption and diet quality in workers aged ≥16 years from 2006 to 2017 in Spain and to evaluate the factors associated with diet quality. A nationwide cross-sectional study was carried out among workers using data from the Spanish National Health Surveys in 2006 (n = 11,068), 2011 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 85 publications
1
3
0
Order By: Relevance
“…Our findings are consistent with those of previous studies showing that temporary employment is associated with unfavorable dietary habits among workers. A similar finding was observed in a cross-sectional study conducted in Spain, where temporary employment showed an inverse association with the Spanish Healthy Eating Index, whereas civil servants and those in permanent employment exhibited a direct association compared to individuals with ongoing contracts [15]. Moreover, previous Korean studies have demonstrated associations between temporary employment and dietary behaviors such as skipping meals, eating alone, and not using nutritional supplements [16,35].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our findings are consistent with those of previous studies showing that temporary employment is associated with unfavorable dietary habits among workers. A similar finding was observed in a cross-sectional study conducted in Spain, where temporary employment showed an inverse association with the Spanish Healthy Eating Index, whereas civil servants and those in permanent employment exhibited a direct association compared to individuals with ongoing contracts [15]. Moreover, previous Korean studies have demonstrated associations between temporary employment and dietary behaviors such as skipping meals, eating alone, and not using nutritional supplements [16,35].…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have shown that those experiencing high job insecurity are more likely to rely on health risk behaviors such as cigarette smoking and alcohol misuse as coping strategies to reduce stress [7,13,14]. Similarly, job insecurity among temporary employees may make them less likely to prepare or consume healthy meals, and individuals may opt to skip meals or consume junk food [15,16,35]. Additionally, high job demands and low resources are core components of job stress experienced by temporary employees, which may shape the dietary habits of workers [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the socioeconomic findings of our study, women, illiterate participants, smokers, housekeeping wives, and married individuals had a higher quality of lunch, insignificantly. In a survey of Spanish workers, being male and smoking tobacco was associated with a lower-quality of diet ( 56 ). In another study on Iranian adults, a higher quality of eating was positively associated with education, being a woman, and reversely associated with smoking and marriage ( 57 ).…”
Section: Discussionmentioning
confidence: 99%